Gastrointestinal cell injury and perceived symptoms after running the Boston Marathon - Kelly, Melani R.; Emerson, Dawn M.; McDermott, Brendon P.; Atkins, Whitley C.; Butts, Cory L.; Laursen, R. Mark; Troyanos, Christopher; Duckett, Andrew; Siedlik, Jacob (Frontiers in Physiology, 2023)
Gastrointestinal (GI) disturbances are a prevalent cause of marathon related complaints, and in extreme cases can promote life-threatening conditions such as exertional heat stroke. Our aim was to study intestinal cell injury [via intestinal fatty acid binding protein (I-FABP)] and perceived GI distress symptoms among marathon runners. We also examined potential risk factors (e.g., inadequate sleep) that could exacerbate GI disturbances in healthy, trained endurance runners. This was a parallel mixed-methods study design. 2019 Boston Marathon participants were recruited via email and subjects completed surveys before the race describing demographics and training history. Participants completed a GI questionnaire to assess presence and severity of symptoms, a survey regarding risk factors (e.g., recent illness, medications) that could promote GI disturbances, and provided a urine sample at three time points (immediately pre-race, post-race, and 24-h post-race). Due to weather, blood samples were only collected immediately and 24-h post-race. A total of 40 runners (males: n = 19, age = 44.9 ± 10.8 years; females: n = 21, age = 44.8 ± 10.6 years) completed this study. I-FABP significantly decreased from post-race (3367.5 ± 2633.5 pg/mL) to 24-h post-race (1657.3 ± 950.7 pg/mL, t (39) = −4.228, p < .001, d = −.669). There was a significant difference in overall GI symptom scores across the three time points (F (2, 39) = 41.37, p < .001). The highest average score occurred post-race (.84 ± .68), compared to pre-race (.09 ± .12) and 24-h post-race (.44 ± .28). Post-race I-FABP (r = .31, p = .048) and post-race urine specific gravity (r = .33, p = .041) were significantly correlated with post-race GI symptom scores. Our study provides further support to the individualized nature of GI disturbances, with participants experiencing a wide range of risk factors that can influence the extent of GI damage and perceived symptoms during and after exercise.